2008
DOI: 10.1515/dmdi.2008.23.1-2.175
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Critical Overview of the Biological Effects of Methylglyoxal and Further Evaluation of a Methylglyoxal-Based Anticancer Formulation in Treating Cancer Patients

Abstract: A historical perspective on methylglyoxal research is briefly presented, mentioning the documented anticancer and antiviral effects of methylglyoxal. The idea and the supporting experimental evidence of Albert Szent-Györgyi et al. that methylglyoxal is a natural growth regulator and can act as an anticancer agent are mentioned. Previously a few in vivo studies suggested safe administration of methylglyoxal. However, recent literature abounds with the toxic effects of methylglyoxal. The authors present a brief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 64 publications
0
20
1
Order By: Relevance
“…Methylglyoxal has also been found to inactivate glyceraldehyde-3-phosphate dehydrogenase (GA3PD), a key enzyme of the glycolytic pathway, and this inactivation is responsible to a significant extent for the inhibition of glycolysis of tumor cells by methylglyoxal (Halder, Ray & Ray, 1993). These findings paved the way for anticancer drug development using methylglyoxal as a key component (Talukdar et al, 2008). Data on the toxicity effects of methylglyoxal in animal studies are however inconsistent (Kalapos, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Methylglyoxal has also been found to inactivate glyceraldehyde-3-phosphate dehydrogenase (GA3PD), a key enzyme of the glycolytic pathway, and this inactivation is responsible to a significant extent for the inhibition of glycolysis of tumor cells by methylglyoxal (Halder, Ray & Ray, 1993). These findings paved the way for anticancer drug development using methylglyoxal as a key component (Talukdar et al, 2008). Data on the toxicity effects of methylglyoxal in animal studies are however inconsistent (Kalapos, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For example, methylglyoxal selectively inhibits mitochondrial respiration and glycolysis in cells [56,57]. It inactivates membrane ATPases and glyceraldehyde-3-phosphate dehydrogenase, a key enzyme of the glycolytic pathway [58,59]. Recently, we have demonstrated that methylglyoxal's posttranslational modification of heat shock protein 27 (HSP27) may play an important role in cell survival in gastrointestinal cancer [60].…”
Section: Methylglyoxal and Methylglyoxal-modified Proteinsmentioning
confidence: 99%
“…11 These findings paved the way for anticancer drug development using MG as a key component. 12,13 A major problem with using MG as an anticancer drug is that MG, being a normal metabolite, is rapidly degraded by various enzymes present in the body. 6,14,15 Hence, shielding MG with convenient nanoparticles may prevent this in vivo degradation, making it more competent as an anticancer drug.…”
Section: Introductionmentioning
confidence: 99%